Performance of the AMBFTK board for the FastTracker processor for the ATLAS detector upgrade - Albertin, Fauzia; Andreani, A.; Annovi, A.; Beretta, M.; Citterio, M.; Crescioli, F.; Dell'Orso, M.; Giannetti, P.; Lanza, A.; Liberali, V.; Magalotti, D.; Meroni, C.; et al. (Journal of Instrumentation, 2013)
Modern experiments at hadron colliders search for extremely rare processes hidden in a very large background. As the experiment complexity and the accelerator backgrounds and luminosity increase we need increasingly complex and exclusive selections. The FastTracker (FTK) processor for the ATLAS experiment offers extremely powerful, very compact and low power consumption processing units for the future, which is essential for increased efficiency and purity in the Level 2 trigger selection through the intensive use of tracking. Pattern recognition is performed with Associative Memories (AM). The AMBFTK board and the AMchip04 integrated circuit have been designed specifically for this purpose. We report on the preliminary test results of the first prototypes of the AMBFTK board and of the AMchip04.
Gesehen am 11.05.2021